1994
DOI: 10.1007/bf00194400
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of factor IX in patients with haemophilia B

Abstract: The aims of this study were to investigate the influence of total blood sampling time on the estimated pharmacokinetic parameters of Factor IX procoagulant activity (FIX:C) and to relate the pharmacokinetics of FIX:C to the putative physiological disposition of Factor IX (FIX). Six patients with severe haemophilia B each received 2 infusions of FIX and on both occasions blood samples were collected for 104 h. Each FIX:C decay curve was processed with successive deletion of the last (remaining) datapoint. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 22 publications
(20 reference statements)
3
11
0
Order By: Relevance
“…These findings are consistent with those of Bjorkman et al ., who described linear changes in factor IX PK parameters with increasing age and body weight [3]. Similarly, the biexponential profile we observed in our profiles is corroborated by previous studies which demonstrate that factor IX concentrations decline in a biphasic pattern [9,10]. Given the complexity regarding factor IX disposition for the time-dependent activity of this protein, a simple PK approach (i.e.…”
supporting
confidence: 89%
“…These findings are consistent with those of Bjorkman et al ., who described linear changes in factor IX PK parameters with increasing age and body weight [3]. Similarly, the biexponential profile we observed in our profiles is corroborated by previous studies which demonstrate that factor IX concentrations decline in a biphasic pattern [9,10]. Given the complexity regarding factor IX disposition for the time-dependent activity of this protein, a simple PK approach (i.e.…”
supporting
confidence: 89%
“…The length of time over which samples are taken differs amongst various studies, and has been found to have a significant impact on half‐life results [ 16, 22]. Since a 48‐h sampling period produces fairly consistent results [ 23], there may have been some merit in extending the sampling time past 24 h in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Dosing and FVIII:C/FIX:C data from pharmacokinetic studies performed during the 1990s (ref. [13,14,25,26] and unpublished data) were also available for some patients. The data collection was monitored by two research nurses who checked a random sample constituting 20% of the CRFs against the primary data sources.…”
Section: Methodsmentioning
confidence: 99%